2015
DOI: 10.1371/journal.pone.0138189
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes, not Osteoblasts or Lining Cells, are the Main Source of the RANKL Required for Osteoclast Formation in Remodeling Bone

Abstract: The cytokine receptor activator of nuclear factor kappa B ligand (RANKL), encoded by the Tnfsf11 gene, is essential for osteoclastogenesis and previous studies have shown that deletion of the Tnfsf11 gene using a Dmp1-Cre transgene reduces osteoclast formation in cancellous bone by more than 70%. However, the Dmp1-Cre transgene used in those studies leads to recombination in osteocytes, osteoblasts, and lining cells making it unclear whether one or more of these cell types produce the RANKL required for osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
224
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(245 citation statements)
references
References 38 publications
13
224
3
5
Order By: Relevance
“…The Dmp1-Cre transgene used in this study also causes recombination in osteoblasts (6,30). We have shown previously that deletion of Tnfsf11 using a Sost-Cre transgene that does not delete in osteoblasts or lining cells leads to the same reduction in osteoclasts as deletion using the Dmp1-Cre transgene (30).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The Dmp1-Cre transgene used in this study also causes recombination in osteoblasts (6,30). We have shown previously that deletion of Tnfsf11 using a Sost-Cre transgene that does not delete in osteoblasts or lining cells leads to the same reduction in osteoclasts as deletion using the Dmp1-Cre transgene (30).…”
Section: Discussionmentioning
confidence: 73%
“…We have shown previously that deletion of Tnfsf11 using a Sost-Cre transgene that does not delete in osteoblasts or lining cells leads to the same reduction in osteoclasts as deletion using the Dmp1-Cre transgene (30). Based on this, we concluded that osteocytes, not osteoblasts or lining cells, are the major source of RANKL involved in oste- Osteocyte RANKL, B Cells, Estrogen, and Bone Loss NOVEMBER 25, 2016 • VOLUME 291 • NUMBER 48 oclast formation.…”
Section: Discussionmentioning
confidence: 74%
“…It was originally believed that osteocytes are quiescent cells in bone matrix, but numerous studies now show that osteocytes play essential roles in bone homeostasis by regulating osteoblasts and osteoclasts (31). For example, osteocytes can regulate osteoclastogenesis by expressing RANKL and its decoy receptor osteoprotegerin (7,(32)(33)(34)(35)(36). Osteocytes can also regulate osteoblast differentiation by secreting sclerostin (SOST), an inhibitor of Wnt signaling (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…RANKL (ligante de RANK) é produzido como fator local por células do ligamento periodontal (osteoblastos e fibroblastos) em resposta a intensas forças ortodônticas. Recentemente, surgiram evidências de que os osteócitos são importante fonte de RANKL para a formação de osso esponjoso (XIONG et al, 2015). O receptor de membrana RANK (receptor activator of Nfk-B) é encontrado em células precursoras de osteoclastos.…”
Section: P a L A V R A S -C H A V Eunclassified
“…Estudos demonstram que mudanças na tensão mecânica, provocada pelas forças ortodônticas, alteram os níveis de OPG e RANKL no ligamento periodontal (KANZAKI et al, 2006;NISHIJIMA et al, 2006;TADDEI et al, 2012) e tecido ósseo (XIONG et al, 2015). A expressão diferenciada desses mediadores, nos sítios de compressão e tensão, responderia por padrões específicos de migração celular e formação/reabsorção de tecido ósseo (LI et al, 2015;TADDEI et al, 2012;ZHANG et al, 2016;ZHOU et al, 2011).…”
Section: Desenvolvimentounclassified